COMPARAÇÃO ENTRE ESTRATÉGIAS NUMÉRICAS PARA MODELAGEM DE BUCHAS COM VISTAS AO CÁLCULO DE FADIGA - Weijh, André; Marczak, Rogério José (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
This paper presents a comparison between different numerical models of mechanical bushings used in cargo transport vehicles as connecting element or transmitting movements and forces. The numerical models are based on the finite element method and different representations of the bushing are analyzed. Fatigue life is evaluated at a point of interest of the component through traditional methods. The importance of correct modeling of these components in numerical models of similar structures largely used in industry is also discussed. As main results have the necessity of bushing modeling in transient analysis, besides the impossibility of utilization of rigid bushing as an alternative industrial way to modeling this component.